The Elastic Properties of Objects by Determining Young's Modulus for the Characterization of Metal Raw Materials Using a Speed Sensor Encoder and a Load Cell Sensor - Umi Pratiwi; Wahyu Tri Cahyanto; Sunardi (CV. Media Digital Publikasi Indonesia, 2023)
The unique characteristic of a metal material can be determined from the value of Young's modulus which represents the ability of the material to deform in response to an external force given to the material. This study aims to determine the value of Young's modulus for three metal wires (copper, nickel, and steel) and the percentage of measurement errors using a self-designed Young's modulus kit equipped with a load cell sensor and speed sensor encoder. The measurement of Young's modulus was carried out in five experiments without any variation in diameter (the diameter was fixed and the same for all metals), and the results were compared with the reference values. The results showed that the values of Young's modulus for copper, nickel, and steel wires were 11.74 x 1010 N/m2, 21.63 x 1010 N/m2, and 20.84 x 1010 N/m2, respectively. The difference between the measured values and the reference values for Young's modulus for copper, nickel, and steel wires were 6.7%, 3.0%, and 4.18%, respectively. The small differences between the measured values and the reference values indicate that the measurement approach approximates the reference values and can be used to support other measurements involving Young's modulus values of a metal material